Leading within systems of inequity in education : a liberation guide for leaders of color - Rice-Boothe, Mary (Arlington, VA : ASCD, 2023)
"This indispensable liberation guide will help leaders of color overcome obstacles and create the path to genuine equity in schools"--
How did we get here? -- How do we stay here? -- Looking inward -- Practicing love, rage, and self-care -- Saying it and naming It -- Creating your coalition -- Taking a stand -- Creating a new school system -- Final thoughts.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 31, 2023).
eBooks on EBSCOhost
Keywords: Minority school administrators -- United States; School management and organization -- Vocational guidance -- United States; Racial justice in education -- United States; Educational leadership -- United States; Educational equalization -- United States; Administrateurs scolaires issus des minorités -- États-Unis.; Administration scolaire -- Orientation professionnelle -- États-Unis.; Leadership en éducation -- États-Unis.; Démocratisation de l'enseignement -- États-Unis.; Educational equalization; Educational leadership; Minority school administrators; Racial justice in education; School management and organization -- Vocational guidance; United States